Daya Tarik Cerita AU (Alternate Universe): Kenapa Banyak yang Lebih Memilih Cerita AU daripada Buku Fisik? - Khasanah, Rima Putri; Kinanti, Nabila Putri; Amalia, Liza Rizqi; Saputri, Reindani Rahayu; Karina (Kajian Bahasa dan Sastra (KABASTRA), 2024)
Currently, the reading interest of the Indonesian people is very low. This phenomenon is happening because most people spend their time surfing on social media, especially Twitter or X than reading physical books. The world of literacy was also shifted by the emergence of online fiction stories such as the Alternate Universe (AU) interesting to research. The purpose of this study is to find out and analyze the reasons why many people choose Alternate Universe (AU) rather than physical books. The research method used is a descriptive method with a qualitative approach. The data source came from questionnaires disseminated via Twitter and randomly sampled. This study's results explain that AU stories attract readers because of their various genres, models, appearances, and creativity. No wonder many people are more interested in reading AU than physical books.